Some Thoughts on Public Policy and Industrial Peace - Downie, Bryan (Relations industrielles / Industrial Relations, 1981)
This paper examines various strategies for industrial peace. Strategies which attack both the root causes of conflict and the effects of labour-management strife are discussed. The author then draws some broad inferences for public policy and for the parties in collective bargaining.